Reconstruction of the logical and communicative argumentation model - Vashko, Oksana A. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
In the article is provided a systematic analysis of the essence of multidimensional phenomenon of argumentation as a logical-communicative model, is substantiated the significance of its logical and communicative components. Based on the analysis, the author identifies ethical-psychological, rhetorical and general methodological components in the communicative level of argumentation. There is offered conventional classification of the optimisation methods of argumentation procedure, used tricks and occurred errors in case of violation of logical rules the conducting an argument under the given components. Based on scientific and educational literature the main techniques, tricks and errors of argumentation are identified, listed and characterised. The provided material will be useful and practically applicable for specialists in the fields of administration, business, management, economics, politics, law, communications and many others, as well as in lecturing logic, argumentation theory and business communication for students and future professionals.
Keywords: argumentation; logical-communicative model of argumentation; logical techniques of argumentation; rhetorical methods of argumentation; psychological and ethical methods of argumentation; general methodological tools of argumentation; logical errors; logical tricks; optimisation of argumentation